Expression of recombinant Manduca sexta prophenoloxidase activating proteinase-1 in Bacillus subtilis - Wang, Wenjing (Kansas State University, 2013)
Prophenoloxidase-activating proteinase (proPAP) activates prophenoloxidase when bacteria or fungi invade Manduca sexta. Upon activation, phenoloxidase initiates synthesis of melaninin, which can encapsulate the invaders and kill them. M. sexta contains three proteases that can activate prophenoloxidase, proPAP1, proPAP2, and proPAP3. The study of proPAP function has been slowed by the difficulty of expressing the proteins in recombinant systems. ProPAP1 contains one clip domain and one serine proteinase domain, a simpler structure than proPAP2 and proPAP3, which have two clip domains. For this reason, proPAP1 was selected for this investigation, to develop an improved system for expression of recombinant proPAP zymogens. In past experiments proPAP1 had a low expression level in insect cells using a baculovirus vector. In Escherichia coli, proPAP1 was expressed as an insoluble protein that could not be refolded successfully. The Bacillus subtilis expression system offers a potential improvement for expression of recombinant clip domain proteases because it can secrete recombinant proteins into the medium, it is a Biosafety Level 1 organism that is easy to handle, and it is less expensive to culture than insect cells. Four constructs for expression of proPAP1 and proPAP1 mutants were produced in the plasmid shuttle vector pHT43, which is compatible with both E. coli and B. subtilis. Experiments were carried out to test and optimize expression and purification of proPAP1 in B. subtilis. Conditions were optimized for IPTG (isopropyl β-D-1-thiogalactopyranoside) concentration, IPTG induction time, growth medium and induction temperature. Results showed that 0.5mM IPTG with 20 hours induction at 37°C in 2xYT medium was the optimum condition for proPAP1 production in the B. subtilis system. The recombinant proPAP1 was precipitated from the medium in 50% saturated ammonium sulfate and partially purified by nickel affinity chromatography. In addition to the full length proPAP1 protein, degradation of proPAP1 was also observed. Further experiments should be done to try to solve this problem. With purified protein, future work can be aimed at study of the structure and function of proPAP1.
Keywords: Manduca sexta; Bacillus subtilis; proPAP1; Biochemistry (0487)